Terapi Humor: Video Komedi terhadap Perubahan Tekanan Darah pada Pasien Hipertensi Primer - Fazlin binti syafruddin; Rahmawati Ramli; Rizqy Iftitah Alam; Akbar Asfar (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Hypertension is characterized by increased blood pressure in the arteries which transport nutrients in the form of blood from the heart to then circulate throughout the body's tissues. Humortherapy has the effect of stimulating a person to laugh, this action can stimulate the release of endogenous opiates or substances commonly known as endorphins. The research design used was a quasi-experimental quasi-pretest posttest control group design with a sample size of 22 intervention and 22 control respondents using random sampling. On the other hand, the Wilcoxon diastolic test intervention group before the hypothesis tested p-value 001 and the Wilcoxon control group systolic-diastolic test before the hypothesis was not normal, so the application of the Wilcoxon test based on data analysis showed a p value of less than 0.001. The results showed that the average diastolic blood before-after diastolic was given 82.73, after 78.64, and the average systolic blood before-after diastolic was 146.82, after 133.18. In contrast, in the control group, the average systolic blood pressure before and after receiving humoral treatment was 145.82 and 135.91. Meanwhile, the average diastolic blood pressure before being given humor therapy and diastolic blood after being given humor therapy was 87.00. conclusion results show that humor therapy can reduce blood pressure in primary hypertension patients